Prison wife stigma: an exploration of stigma by affiliation and strategic presentation of self - Moore, Heather D. (Kansas State University, 2016)
The stigma of prison extends beyond the male prisoner to those who care about him, often his wife. Almost all prisoners will be released back into their communities (Hughes, 2003) and having a solid support network improves successful re-entry experiences and lowers recidivism rates for men who are released from prison (Duwe & Clark, 2013). The stigmatization that prison wives feel because they are married to an inmate, can affect how attached they feel to their community, how comfortable they feel in their workplace, and how accepted they feel by their family and friends. Financial exploitation, challenging prison policies, and visitation procedures oftentimes can make an already difficult situation even more difficult. While the number of men in prison in the United States is slowly declining, the United States remains the world leader in the number of people incarcerated (Travis, et. al., 2014). As this level of incarceration continues to affect such a large number of people (specifically women for this research) in our society, there is reason to consider a more intentional approach to focusing on recognizing the feelings and experiences of prison wives. This research includes narrative interviews of 35 women who identified as prison wives. The goal of the research was to specifically gather details on their experiences of being a prison wife and how they feel that society judged them based on the stereotype they perceived society to have. My research shows that the interviewees feel stigmatized; however, the awareness of, feelings about, and the reaction toward the stigmatization manifests differently among the two groups of prison wives that I identified: Riders and Stoppers. I have gathered details about how their experiences were often made more challenging as they tried to maintain their relationships in the midst of financial exploitation and challenging prison policies and procedures. I conclude my thesis on the relevancy of their experiences as they relate to the prison-industrial complex in our society and how this affects their interactions within the communities in which a prisoner’s wife, family members, and formerly incarcerated individuals live and work.
Keywords: Presentation of Self; Stigma; Sociology; Criminology; Prison-Industrial ComplexPrison Wives